Increased Competence in The Performance of Government Apparatus At the Social Service of East Java Province - Ach. Resa Fachrizi; Sri Pantja Madyawati (Al-Amien Prenduan for Islamic Institute, 2023)
According to the target, the targets of employee performance in the East Java Provincial Social Service cannot all be realized. The competence of Social Service personnel still needs to be improved, considering that social services are agencies that have the main task of social service and rehabilitation for people with social welfare problems. Analyze the extent of the improvement of the competence of Social Service employees and examine factors that affect the improvement of employee competence. The type of research used in research is a type of descriptive qualitative research. The sampling technique used in this study is purposive sampling, in this study, the informants are the Head of Social Services, the Secretary, and all Heads of Fields in the Social Service. Findings in the field show that the increase in competence carried out by the East Java Provincial Social Service to its personnel is still not optimal. This is due to several factors that hinder the improvement of personnel competence, including Trust and values, expertise, experience, personal characteristics, motivation, emotional issues, and intellectual capacity. The study concludes that the improvement of competence carried out on Social Service personnel is limited to attending work meetings, technical meetings, congresses, seminars, technical guidance, and workshops. Knowledge (knowledge) at least the social service apparatus related to tasks, principals and functions, work programs, and stages in carrying out work programs, not all personnel understand. The skills of the social service apparatus that must be possessed are the ability to compile, manage, evaluate programs and performance, manage finances and assets, and the ability to communicate, adapt and manage archives and information.